Improving Athlete Performance Through Technology-Based Sports Learning Innovation - Andika Marsuki; Andi Wirawan Risal; Ians Aprilo; Muhammad Sulfa; Ferdinandus Ardian Ali (Jurnal Ilmu Keolahragaan, 2025)
Innovation in sports learning is increasingly important to enhance athlete performance through advanced technologies and personalized training methods. Research in this area explores effective strategies to integrate technology for optimized sports education. This study aims to investigate the role and impact of technology-based innovations in sports learning to improve athlete performance. The study employed a library research approach, which involves systematically collecting and analyzing existing literature, journals, and academic sources related to sports learning innovation. Library research enables a comprehensive review of current knowledge and trends without new experimental data collection. Findings indicate that technological tools such as video analysis to virtual reality, artificial intelligence, and mobile applications significantly enhance athletes learning experiences and performance outcomes by enabling personalized and accessible training. The integration of technology also fosters interactive and immersive learning environments supporting better skill acquisition and motivation. The study highlights the necessity of adopting innovative technological methods in sports education to meet athletes individual needs and improve training effectiveness. It also emphasizes library research as a critical method to synthesize existing knowledge for advancing sports learning innovation. However, challenges such as the availability and accessibility of technology and complex data management still need to be addressed. Thus, technology will continue to drive progress in sports training and help athletes and coaches in the future.